تحديد الاحتياجات التدريبية في بناء الاختبارات التحصيلية لأساتذة التعليم المتوسط - عزي، إيمان; إسعادي، فارس; رابحي، إسماعيل Rabehi, Ismail (جامعة قاصدي مرباح - ورقلة, 2018)
The present study aimed to identify the needs of the teachers of intermediate education training in the field of building the tests of achievement and the study started from the following question: - What are the training needs of middle school teachers in building achievement tests? To answer the question, a tool was constructed by the student to determine the needs of the training teachers and after confirming their validity, they were applied to the sample of the study which is composed of the teachers of intermediate education in the institutions of the valley. - There are training needs for middle school teachers on how to build achievement tests. - There are training needs of the teachers of the intermediate education in the discharge and analysis of the results of the achievement tests. - There are training needs of middle school teachers in interpreting the results of students in the achievement tests.
هدفت الدراسة الحالية للتعرف على احتياجات أساتذة التعليم المتوسط التدريبية في مجال بناء الاختبارات التحصيلية وعليه انطلقت الدراسة من التساؤل التالي: - ما هي الاحتياجات التدريبية لأساتذة التعليم المتوسط في بناء الاختبارات التحصيلية؟ للإجابة عليه تم بناء أداة من طرف الطالبة لتحديد احتياجات الأساتذة التدريبية وبعد التأكد من صلاحيتها تم تطبيقها على عينة الدراسة المتكونة من أساتذة التعليم المتوسط بمؤسسات الوادي مركز وتم التوصل إلى النتائج التالية: - هناك احتياجات تدريبية لأساتذة التعليم المتوسط في كيفية بناء الاختبارات التحصيلية. - هناك احتياجات تدريبية لأساتذة التعليم المتوسط في تفريغ وتحليل نتائج الاختبارات التحصيلية. - هناك احتياجات تدريبية لأساتذة التعليم المتوسط في تفسير نتائج التلاميذ في الاختبارات التحصيلية.
Keywords: التعليم المتوسط -- التحصيل العلمي -- الاختبارات التحصيلية -- الاحتياجات التدريبية